2005
DOI: 10.1175/jcli3525.1
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Broadband Longwave Downwelling Radiative Fluxes, Cloud Radiative Forcing, and Fractional Cloud Cover over the South Pole

Abstract: Annual cycles of downwelling broadband infrared radiative flux and spectral downwelling infrared flux were determined using data collected at the South Pole during 2001. Clear-sky conditions are identified by comparing radiance ratios of observed and simulated spectra. Clear-sky fluxes are in the range of 110-125 W m Ϫ2 during summer (December-January) and 60-80 W m Ϫ2 during winter (April-September). The variability is due to day-to-day variations in temperature, strength of the surface-based temperature inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 36 publications
6
51
0
Order By: Relevance
“…However, these changes are much smaller than the large improvements gained in the prediction of overcast conditions, which have the most impact on aircraft operations. Additionally, other tests (not shown) demonstrate that the model rarely predicts CF that falls in the partly cloudy range, but rather tends to predict overcast and clear conditions instead, in agreement with the known U distribution of observed cloud cover at South Pole station (Town et al 2007). Thus, the forecast skill is the lowest for the partly cloudy sky coverage regardless of the empirical algorithm employed.…”
Section: B Cloud Fractionsupporting
confidence: 68%
See 3 more Smart Citations
“…However, these changes are much smaller than the large improvements gained in the prediction of overcast conditions, which have the most impact on aircraft operations. Additionally, other tests (not shown) demonstrate that the model rarely predicts CF that falls in the partly cloudy range, but rather tends to predict overcast and clear conditions instead, in agreement with the known U distribution of observed cloud cover at South Pole station (Town et al 2007). Thus, the forecast skill is the lowest for the partly cloudy sky coverage regardless of the empirical algorithm employed.…”
Section: B Cloud Fractionsupporting
confidence: 68%
“…Notably, there is a much more marked seasonal cycle at South Pole station; the bias during austral fall is small and positive (0.048), while the bias is much farther from zero during the summer (Ϫ0.250). However, the positive bias in fall may be related to a known negative bias in observed CF compared against independent data (Town et al 2007). Incorporating the modified CF algorithm again substantially reduces the mean bias to Ϫ0.004, effectively centering the error distribution over zero, with these changes being highly statistically significant ( p Ͻ 0.001; Table 1).…”
Section: B Cloud Fractionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, over a high albedo surface, such as the ice or snow cover of Antarctica, low clouds can be warming at any time of year. The study by Town et al (2005) describes the radiative fluxes and cloud radiative forcing over the South Pole in detail. Studies in the Arctic though have found that over a brief period in summer the cooling effect due to cloud shading is stronger than the warming caused by the clouds' greenhouse effect (Shupe and Intrieri, 2004).…”
Section: Motivationmentioning
confidence: 99%